Juxtacortical susceptibility changes in progressive multifocal leukoencephalopathy at the gray–white matter junction correlates with iron-enriched macrophages. (December 2021) - Mahajan, Kedar R; Amin, Moein; Poturalski, Matthew; Lee, Jonathan; Herman, Danielle; Zheng, Yufan; Androjna, Caroline; Howell, Mark; Fox, Robert J; Trapp, Bruce D; Jones, Stephen E; Nakamura, Kunio; et al.
Objective: Describe magnetic resonance imaging (MRI) susceptibility changes in progressive multifocal leukoencephalopathy (PML) and identify neuropathological correlates. Methods: PML cases and matched controls with primary central nervous system lymphoma (PCNSL) were retrospectively identified. MRI brain at 3 T and 7 T were reviewed. MRI-pathology correlations in fixed brain autopsy tissue were conducted in three subjects with confirmed PML. Results: With PML ( n = 26 total, n = 5 multiple sclerosis natalizumab-associated), juxtacortical changes on susceptibility-weighted imaging (SWI) or gradient echo (GRE) sequences were noted in 3/3 cases on 7 T MRI and 14/22 cases (63.6%) on 1.5 T or 8/22 (36.4%) 3 T MRI. Similar findings were only noted in 3/25 (12.0%) of PCNSL patients (odds ratio (OR) 12.83, 95% confidence interval (CI), 2.9–56.7, p < 0.001) on 1.5 or 3 T MRI. On susceptibility sequences available prior to diagnosis of PML, 7 (87.5%) had changes present on average 2.7 ± 1.8 months (mean ± SD) prior to diagnosis. Postmortem 7 T MRI showed SWI changes corresponded to areas of increased iron density along the gray–white matter (GM-WM) junction predominantly in macrophages. Conclusion: Susceptibility changes in PML along the GM-WM junction can precede noticeable fluid-attenuated inversion recovery (FLAIR) changes and correlates with iron accumulation in macrophages.